Attitudes and Perceptions of Tobacco-Related Products in College Students - Yen H. Dang (University of Minnesota Libraries Publishing, 2020)
Background - Despite the highly publicized health consequences, some college students do not perceive tobacco consumption as harmful. Historically-Black College and Universities (HBCUs) have the lowest rates of tobacco-free policies compared to other colleges, universities, and minority-serving institutions, making their students at higher risk for tobacco abuse. A campus Alcohol, Tobacco, and Other Drug Prevention Committee (ATDP) was formed and led by a pharmacist to develop all tobacco cessation policies at the HBCU. Objectives - (1) To determine the knowledge and attitudes of cigarettes, cigars, smokeless tobacco, electronic cigarettes, and hookah among college students in a rural area with high tobacco usage; (2) To assess perceptions on the effectiveness of smoking cessation resources on the college campus led by the ATDP committee. Methods - A cross-sectional study was conducted on 99 students between 18 - 26 years attending a HBCU in Maryland. The online survey was disseminated to assess student's health behaviors and attitudes towards tobacco products and their successfulness in abstinence using campus resources with the Health Belief Model. Results - Participants had more perceived harms with smoking tobacco (cigarettes and cigars) and smokeless tobacco, and greater perceived benefits with using electronic cigarettes and hookah (P < 0.001). Most students had limited knowledge of the four tobacco categories (5.8 ± 2.6 on a 10-point Likert scale). Self-efficacy to quit was 4.2 ± 1.7 on a 10-point Likert scale despite the current resources at the HBCU. Conclusion - Students had a perceived benefits sequential rank order with hookah, e-cigarettes, smokeless tobacco, followed by smoking tobacco. Campuses should investigate barriers for abstinence, raise awareness about the dangers of tobacco, and create programs that enhance self-efficacy when quitting. Innovation and Practice Implication - This is the first study of its kind that compares all major tobacco products head-to-head in a rural and underrepresented population. Additionally, the development of a campus-wide tobacco policy was novel as it was pharmacist-led. The results show this population has limited knowledge of tobacco products with more perceived benefits among newer nicotine delivery systems. Targeted education and public health programs should be implemented to prevent this susceptible group from initiating and continuing tobacco products.   Article Type: Original Research